Answer :
Answer:
I suppose it should be
6b² and (6b²)²
or
6b² and 36[tex]b^{4}[/tex]
Step-by-step explanation:
(a+b)² = a² + 2ab + b²
therefore
(6b²+2a)² = (6b²)² + 12ab² + 4a²
The missing information to make the equality true are 3b² and (3b²)². This can be obtained by using the algebraic identity (x+y)² =x² + 2xy + y².
Find the missing information:
Let the missing information be p and p²
Then the given equation will be: (p+2a)² =p² + 12ab² + 4a²
The algebraic identities is (x+y)² =x² +2xy+y²
Comparing the given equation with the algebra formula we get
y=2a
2xy =12ab² ⇒2x(2a) = 12 ab² ⇒ x = 3b²
Therefore the given equation will be
(3b²+2a)² = (3b²)²+12ab²+4a²
Hence the missing information to make the equality true are 3b² and (3b²)².
Learn more about algebraic identities here:
brainly.com/question/4201440
#SPJ2